2021
DOI: 10.1002/adma.202100272
|View full text |Cite
|
Sign up to set email alerts
|

Orthorhombic Cobalt Ditelluride with Te Vacancy Defects Anchoring on Elastic MXene Enables Efficient Potassium‐Ion Storage

Abstract: The fast and reversible potassiation/depotassiation of anode materials remains an elusive yet intriguing goal. Herein, a class of the P‐doping‐induced orthorhombic CoTe2 nanowires with Te vacancy defects supported on MXene (o‐P‐CoTe2/MXene) is designed and prepared, taking advantage of the synergistic effects of the conductive o‐P‐CoTe2 arrays with rich Te vacancy defects and the elastic MXene sheets with self‐autoadjustable function. Consequently, the o‐P‐CoTe2/MXene superstructure exhibits boosted potassium‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 69 publications
1
84
0
Order By: Relevance
“…The low R ct value in the case of Fe 3 O 4 /MXene-7 reflects the hybrid system’s capability to support faster electron transportation, thereby resulting in improved rate capability. Moreover, a higher slope of the straight line was observed for Fe 3 O 4 /MXene-7, indicating its better Li + diffusion capability …”
Section: Resultsmentioning
confidence: 94%
“…The low R ct value in the case of Fe 3 O 4 /MXene-7 reflects the hybrid system’s capability to support faster electron transportation, thereby resulting in improved rate capability. Moreover, a higher slope of the straight line was observed for Fe 3 O 4 /MXene-7, indicating its better Li + diffusion capability …”
Section: Resultsmentioning
confidence: 94%
“…To ensure a suitable cathode-to-anode capacity ratio for proper cell balance, a cathode-limited configuration was chosen with a cathode-to-anode mass loading ratio of 1:1. [37,38] The capacity and energy density were calculated based on the mass of cathodes. [39,40] The galvanostatic charge/discharge (GCD) tests were measured on a Land battery tester (CT200A).…”
Section: Methodsmentioning
confidence: 99%
“…The density-of-states patterns indicated that P⊂NiTe 2−x had strong metallic features because of continuous electronic states at the Fermi level, accompanied by increasing density-of-states intensities relative to those for NiTe 2−x and NiTe 2 (Figure S12b, Supporting Information). [33] High-resolution Ni 2p X-ray photoelectron spectroscopy (XPS) of MSC/NiTe 2 was deconvoluted into two bonds at 873.3 eV (2p 1/2 ) and 855.6 eV (2p 3/2 ), revealing the presence of Ni 2+ (Figure 3d). Ni (2p) satellite peaks at 881.3 and 861.3 eV, attributed to the Ni (d8) orbital, confirmed bivalent Ni in NiTe 2 .…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%